Georg Simon: Sucher, Prediger, Dichter. Nikolai F. Grundtvig, Erneuerer der dänischen Kirche - Bugge, Knud Eyvin (Grundtvig-studier, 1967)
Georg Simon: Sucher, Prediger, Dichter. Nikolai F. Grundtvig, Erneuerer der dänischen Kirche (Berlin 1965). Reviewed by Knud Eyvin Bugge.The book is divided into two main sections. The first and most copious is an account of Grundtvig’s life, unfortunately with numerous inaccuracies. The second section which offers an introduction into Grundtvig’s world of ideas— the main stress being laid on his theological and religious views—is more successful however.But the aim of the book is really to illustrate how a profound joy, resting upon the victory of Jesus Christ over sin and death, characterizes Grundtvig’s idea of Christianity. It is the hope of the author that the German Church will let itself be instructed by Grundtvig in this respect. Knowing that it was published in East Germany where the conditions of the Church may at times appear rather joyless one cannot help being moved by this ending of the book.